THE EXPERIENTIAL INGREDIENT IN COLLEGE LEARNING (A PHYSICAL EDUCATOR'S PERSPECTIVE) - Luis Fernando Aragón Vargas (Pensar en Movimiento)
This editorial is an essay, reflecting on the role that experiences play in the learning process of college students. A small collection of anecdotes is used to illustrate a few basic concepts of experiential learning: the danger of incomplete learning resulting in a false sense of security; the importance of the intriguing question and how that intriguing question translates into the teaching of sports and physical education skills; the power of emotions in the learning process; the extension of experiences beyond the particular skills involved; and the need to supplement experiences with reflection, assimilation and model development, where the person with a teaching role needs to be always intentional or goal-oriented.